Design and validation of thematic e-modules: optimization of problem solving-based learning - Delawanti Chrisyarani, Denna; Sulistyowati, Prihatin (Universitas Nusantara PGRI Kediri, 2022)
Preparing for learning well is the teacher's obligation, especially in this COVID-19 pandemic. One thing that needs to be considered is compiling appropriate teaching materials. The purpose of this research is to design and validate the thematic e-module design and material based on problem-solving for 3rd-grade elementary school students. This research design used the Borg & Gall development model. The stages are: (1) initial study and collecting data, (2) creating an activity framework, (3) developing product drafts, (4) validation tests, (5) revising validation results. The research instrument is a content and design validation questionnaire. The results of this research are problem-solving-based thematic e-modules. The module presentation was systematic consists of Mapping Basic Competencies, Mapping Indicators, Learning Objectives, Let's Read, Let's Tell a Story, Let's Observe, Let's Discuss, Let's Write, Let's Practice, Conclusion. The results of material validation are 93% in the very valid category and 91% of media validation results are very valid categories so that they can be used in learning